Brain‐specific ablation of Efr3a promotes adult hippocampal neurogenesis via the brain‐derived neurotrophic factor pathway. Issue 5 (13th February 2017) - Qian, Qi; Liu, Qiuji; Zhou, Dongming; Pan, Hongyu; Liu, Zhiwei; He, Fangping; Ji, Suying; Wang, Dongpi; Bao, Wangxiao; Liu, Xinyi; Liu, Zhaoling; Zhang, Heng; et al.
ABSTRACT: Efr3 is a newly identified plasma membrane protein and plays an important role in the phosphoinositide metabolism on the plasma membrane. However, although it is highly expressed in the brain, the functional significance of Efr3 in the brain is not clear. In the present study, we generated Efr3a f/f mice and then crossed them with Nestin‐Cre mice to delete Efr3a, one of the Efr3 isoforms, specifically in the brain. We found that brain‐specific ablation of Efr3a promoted adult hippocampal neurogenesis by increasing survival and maturation of newborn neurons without affecting their dendritic tree morphology. Moreover, the brain‐derived neurotrophic factor (BDNF)‐tropomyosin‐related kinase B (TrkB) signaling pathway was significantly enhanced in the hippocampus of Efr3a‐deficient mice, as reflected by increased expression of BDNF, TrkB, and the downstream molecules, including phospho‐MAPK and phospho‐Akt. Furthermore, the number of TUNEL + cells was decreased in the subgranular zone of dentate gyrus in Efr3a‐deficient mice compared with that of control mice. Our data suggest that brain‐specific deletion of Efr3a could promote adult hippocampal neurogenesis, presumably by upregulating the expression of BDNF and its receptor, TrkB, and therefore provide new insight into the roles of Efr3 in the brain. —Qian, Q., Liu, Q., Zhou, D., Pan, H., Liu, Z., He, F., Ji, S., Wang, D., Bao, W., Liu, X., Liu, Z., Zhang, H., Zhang, X., Zhang, L., Wang, M., Xu, Y., Huang, F., Luo, B., Sun B. Brain‐specific ablation of Efr3a promotes adult hippocampal neurogenesis via the brain‐derived neurotrophic factor pathway. FASEB J. 31, 2104–2113 (2017). www.fasebj.org